Muscle Creatine Kinase (M-CK), Aldolase A and Voltage Dependent Anion Channel 2 (VDAC2) as Potential Biomarkers for Identification of Electrically Stimulated Chicken Muscle - Amid, Azura; Abu Samah, Norshahida; Yusof, Faridah (Journal of Pure and Applied Microbiology, 2014)
Water bath stunning in commercial slaughter houses is a common practice and economical. However, the conditions applied for the stunning process may vary from one slaughterhouse to another and has opened up doors for food adulteration to take place. In this study, proteomics approaches have been used to study the effect of different current and voltages during stunning on the protein expression of the chickens. Protein profiles of the chickens muscle were constructed in order to detect any dufferences in protein expression and modifications. The protein muscle profiles of stunning conditions were compared to the non-stunned. After analysis using 2D Platinum ImageMaster 6.0 software and mass spectrometry identification, Muscle creatine kinase (M-CK), AldolaseA and Voltage Dependent Anion Channel 2 (VDAC2) were identified to be over expressed in the muscle sample of stunned chicken. The over expression of candidate proteins was confirmed at the transcriptional level of RNA expression by Real Time PCR. In conclusion, all three candidate proteins may serve as potential biomarkers for electrically stimulated chicken’s muscle. The existence of these biomarkers will help to monitor the slaughtering and stunning process in future.